Soft Biomorph Actuators Enabled by Wafer‐Scale Ultrathin 2D PtTe2 Layers. Issue 3 (12th October 2021) - Okogbue, Emmanuel; Mofid, Sohrab Alex; Yoo, Changhyeon; Han, Sang Sub; Jung, Yeonwoong
Abstract: Biomorph actuators composed of two layers with asymmetric thermal expansion properties are widely explored owing to their high mechanical adaptability. Electrothermal nanomaterials are employed as the Joule heating components in them for controlled thermal expansion, while their large integration thickness often limits resulting actuation performances. This study reports high‐performance ultrathin soft biomorph actuators enabled by near atom‐thickness 2D platinum ditelluride (PtTe2 ) layers—a new class of emergent metallic 2D transition metal dichalcogenides. The actuators employ wafer‐scale 2D PtTe2 layers sandwiched in between two polymer films of largely mismatched thermal expansion coefficients, which are electrically biased to generate Joule heating. This electrical‐to‐thermal conversion causes the asymmetric expansion of the polymers achieving outstanding actuation motions; i.e., large bending curvature, fast responsiveness, as well as high reversibility and endurance, which surpass the performances of previously explored graphene‐based actuators with much smaller dimensions. Furthermore, the 2D PtTe2 layers‐enabled actuators are demonstrated to function as soft grippers in lifting and relocating heavier objects, implying the great potential of near atom‐thickness materials in biomimetic devices. Abstract : A new type of bimorph actuators operating by the Joule heating of near atom thickness 2D PtTe2 layers sandwiched between two distinct polymers of mismatched thermal expansion properties is reported.